(3QSGdI LGeYI GdCdaGX GdLeYs - (3GdQHGVjs ((3YHO GdaJGM Hf MSf Hf eMehO Hf CMeO Hf MSf GdehUdi s)
(3ChdgG (B:s
(3gPg QSGdI ddQHGVi hHYO , agPg LGeYI GdCdaGX ai GdYQHjI HGdLeY GYJHGQkG ddCLRGA cGdEaQGO fWaI CeTGL LeY eTL Ch eTL deGA GdQLGd jNJdW HeGA GdeQCI s
(3BNQgG (B:s
(3GSJbOeJg ef bhdg fbVJ YRdgG CfcGKkG EfeG bGdhG KhH CNdGa CQGOhG Cf fhGUjI CNdGa SQGhjd CSeGW Ci ZjQ eMThI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B- (3GdehUd (B(249) s
Keywords: (3GddZIs